Electronics V - Green, D.C (Longman Scientific & Technical, 1993)
Electronics V provides a thorough coverage of the design of analogue and digital circuits. It has been written at a level consistent with BTEC Higher Certificate/Diploma and first year degree courses in electronic engineering. Emphasis is firmly placed on the design of circuits and the choice of devices for specific applications, rather than on analysis of circuits. Of particular importance are the chapters on programmable logic devices, increasingly used in modern electronic systems, and on interconnecting high-speed digital circuits.